Lecciones de una experiencia de participación campesina en un proceso de restauración ecológica en el Parque Nacional Natural Las Orquídeas, Colombia (2013)
ABSTRACT: The formulation of strategies for conservation and sustainable use of biodiversity are a focus for discussion in protected areas overlapping with family farms. The purpose of this study was to identify the factors affecting farmer participation in an ecological restoration project promoted by Las Orquídeas National Natural Park, located west of the department of Antioquia. The results reveal that the people is afraid of expropriation and distrusts technicians, and that there are communication failures, economic and cultural obstacles to limit cattle farming and social restrictions to intensify the exploitation of labour force demanded by new technologies proposed by the Park.